PERANAN ORANG TUA DALAM MENINGKATKAN MOTIVASI BELAJAR ANAK (Studi Terhadap Anak dalam Keluarga di RT.03 RW.013 KELURAHAN SIDOMULYO TIMUR KECAMATAN MARPOYAN DAMAI PEKANBARU) - Arif, Furqan; Natuna, Daeng Ayub; Sumardi, Sumardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to find out that education is a process of educating and guiding students to achieve certain goals in the form of positive changes in children. The changes in question are part of an ongoing process of maturity, which ultimately manifests the maturity of children. The formulation of the problem in this research is how high the role of parents in improving children's learning motivation in RT.03 RW.013 East Sidomulyo Subdistrict Marpoyan Damai Sub-district Pekanbaru City, how high the motivation to learn child in RT.03 RW.013 East Sidomulyo Sub-District Marpoyan Damai Sub- Pekanbaru City, How much influence the role of parents to the motivation of learning children in RT.03 RW.013 Village East Sidomulyo Marpoyan Damai Sub-district Pekanbaru City In accordance with the Formulation of Problems So The Purpose of This Research Is To determine the role of parents in improving children's learning motivation in RT .03 RW.013 eastern sub-district of sidomulyo marpoyan sub-district pacar kota Pekanbaru To find out the level of learning motivation of children in RT.03 RW.013 kelurahan sidomulyo east marpoyan sub-district peace of the city Pekanbaru, To find the great influence of parent role on learning motivation of children in RT.03 RW.013 kelurahan sidomulyo east sub district marpoyan pacific city Pekanbaru .Keywords: Role of Parents, Improving Motivation, Learning Children